Investigating the influence of elevated temperature on nutritional and yield characteristics of mung bean (Vigna radiata L.) genotypes during seed filling in a controlled environment - Priya, Manu; Bhardwaj, Anjali; Jha, Uday Chand; HanumanthaRao, Bindumadhava; Prasad, P. V. Vara; Sharma, Kamal Dev; Siddique, Kadambot H.M.; Nayyar, Harsh (Frontiers in Plant Science, 2023)
Rising temperatures impact different developmental stages of summer crops like mung bean, particularly during the crucial seed-filling stage. This study focused on two mung bean genotypes, categorized as heat-tolerant [HT] or heat-sensitive [HS]. These genotypes were grown in pots in an outdoor natural environment (average day/night temperature 36/24.3°C) until the onset of podding (40 days after sowing) and subsequently relocated to controlled-environment walk-in growth chambers for exposure to heat stress (42/30°C) or control conditions (35/25°C) until maturity. For all measured attributes, heat stress had a more pronounced effect on the HS genotype than on the HT genotype. Heat-stressed plants exhibited severe leaf damage, including membrane damage, reduced chlorophyll content, diminished chlorophyll fluorescence, and decreased leaf water content. Heat stress impeded the seed-filling rate and duration, decreasing starch, protein, fat, and mineral contents, with a notable decline in storage proteins. Heat stress disrupted the activities of several seed enzymes, inhibiting starch and sucrose accumulation and consequently decreasing individual seed weights and seed weight plant-1. This study revealed that heat stress during seed filling severely impaired mung bean seed yield and nutritional quality due to its impact on various stress-related traits in leaves and enzyme activities in seeds. Moreover, this research identified potential mechanisms related to heat tolerance in genotypes with contrasting heat sensitivity.